Numerical Modeling of Renal Ionic Equilibrium for Implantable Kidney Applications - Saleh Massoud; Ayham Darwich; Ebrahim Ismaiel (مجلة بغداد للعلوم, 2023)
The human kidney is one of the most important organs in the human body; it performs many functions and has a great impact on the work of the rest of the organs. Among the most important possible treatments is dialysis, which works as an external artificial kidney, and several studies have worked to enhance the mechanism of dialysate flow and improve the permeability of its membrane. This study introduces a new numerical model based on previous research discussing the variations in the concentrations of sodium, potassium, and urea in the extracellular area in the blood during hemodialysis. We simulated the differential equations related to mass transfer diffusion and we developed the model in MATLAB Simulink environment. A value of 700 was appeared to be the most appropriate as a mass transfer coefficient leading to the best permeability. The suggested models enabled to track the temporal variations of urine, K and Na concentrations in blood streamline. This also produced the time needed to reach the requested concentrations mentioned in literature studies (960 ms). Concentrations evaluation was performed with error rates not exceeding 2% for all ions compared to the normal values of human blood.The current work presents the first step towards combinig the mass transfer and diffusion principles with our efforts in designing and implementing an electrophoresisbased implantable kidney.